A comparison of the functional results and costs of functional cast and volar-flexion ulnar deviation cast at 2-year follow-up in 105 patients aged 65 and older with dorsally displaced distal radius fracture: A randomized controlled trial - Ax Maarit; Reito Aleksi; Hevonkorpi Teemu P; Palola Vili; Kukkonen Juha; Luokkala Toni; Laitinen Minna K; Launonen Antti P; Mattila Ville M (PUBLIC LIBRARY SCIENCE, 2025)
Background and purpose: Non-operative treatment is the most common treatment option for older patients with distal radius fracture (DRF). Traditionally, wrists have been placed in volar-flexion and ulnar deviation position (VFUDC). In recent years, there has been a trend towards using a functional position cast (FC). However, long-term results for these different casting positions are lacking.
Patients and methods: This randomized, controlled, prospective study evaluates the functional results and costs of the 2 casting positions in patients 65 and older with DRF. Primary end point in this study was Patient-Reported Wrist Evaluation (PRWE) at 24 months, and secondary end points were cost-effectiveness of treatment, health-related quality of life measurement (15D), short version of Disabilities of arm, shoulder and hand score (QuickDASH), and VAS at 24 months. The trial was registered in ClinicalTrials.gov (NCT02894983, https://clinicaltrials.gov/ct2/show/NCT02894983).
Results: We enrolled 105 patients, of which 81 (77%) continued until 24-month follow-up. 8 patients (18%) were operated in the VFUDC group and 4 (11%) in the FC group. Patients in the VFUDC group also received more frequent physical therapy. The difference in PRWE score between the VFUDC and FC groups at 24 months was -4.31. The difference in the cost of treatment per patient was €590. Both findings favored FC.
Interpretation: We found a slight, but consistent difference in the functional results between groups. These results suggest that VFUDC is not superior to FC when treating Colles' type DRF. Cost analysis revealed overall costs in the VFUDC group are nearly double those in the FC group, mostly due to more physical therapy, additional visits to hospital, and additional examinations. Therefore, we recommend FC in older patients with Colles' type DRF.